Effects of Continuing Professional Development on Nurses’ Competence in Chronic Illness Care: A Systematic Review and Meta-Analysis - Miming Oxyandi; Aris Citra Wisuda; Faridah Mohd Said; Rhipiduri Rivanica (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Chronic illnesses, including diabetes mellitus, hypertension, cardiovascular disease, and cancer, represent major global health challenges requiring sustained nursing competence. Continuing Professional Development (CPD) is promoted to enhance nurses’ knowledge, skills, and professional attitudes; however, its effectiveness in chronic illness care remains inconsistent. This meta-analysis evaluated the impact of CPD on nursing competence in managing chronic illnesses. A systematic search of PubMed, Scopus, CINAHL, and Web of Science was conducted for studies published between January 2019 and January 2025. Eligible studies included randomized controlled trials, quasi-experimental, and cohort designs reporting competence-related outcomes following CPD interventions. Data were synthesized using a random-effects model, and heterogeneity was assessed using the I² statistic. Eleven studies involving 1,362 nurses from Asia, Europe, and the Americas met the inclusion criteria. CPD showed a significant positive effect on nursing competence in chronic illness care (Hedges’ g = 0.47; 95% CI: 0.31–0.63; p < 0.001). E-learning and blended learning approaches were more effective than traditional face-to-face methods, and programs lasting more than six months produced greater improvements. Moderate heterogeneity was observed (I² = 48%), with no evidence of publication bias. The findings indicate that CPD moderately improves nursing competence, particularly when delivered through technology-enhanced and sustained educational strategies. Variations in intervention duration and learning modality may explain differences in effect sizes across studies. CPD is an effective strategy to strengthen nursing competence in chronic illness care, especially when implemented through blended or e-learning formats and extended program duration Keywords: Continuing Professional Development, Nursing, Competence, Chronic Illness Care, Meta-Analysis